Mechanisms linking school physical education policies to college students’ physical activity: an empirical test of a moderated mediation model - Liu, Ming; Liu, Huanju; Qin, Zhuzhu; Tao, Yining; Jiang, Ruizhe; Zhong, Yanxia; Ye, Wan; Ye, Xinxin (Frontiers in Psychology, 2026)
School physical education policies (SPEPs) promote college students’ physical activity and fitness, but the mechanisms linking policy to behavior are under-explored. This study explores how SPEPs influence physical activity, focusing on time management’s mediating role and grit’s moderating effect. A survey of 1,151 students from six universities used scales measuring attitudes, time management, grit, and physical activity. Results showed males scored higher in physical activity, time management, and grit. SPEPs indirectly influence physical activity through time management, with grit moderating this pathway. Recommendations include enhancing policy support, time management training, fostering positive psychological traits, and gender-sensitive interventions.